Collins World Atlas (London HarperCollins Publishers, 2003)
This budget title is up-to-date, clear and accessible. The contents have been carefully planned to provide balanced map coverage of the world and all the essential information required in a budget atlas for family, study and business use.
Include Maps and Index.
Keywords: Atlases, British -- World maps -- Atlases